Communication, Resources, Disposition, and Bureaucracy: Evaluating the Smart Indonesia Program Implementation at SMA Negeri 1 Sungai Lilin - Nursilawati Nursilawati; Nila Kesumawati; Dessy Wardiah (Journal of Social Work and Science Education, 2026)
This study examines the implementation of Indonesia's Smart Indonesia Program (Program Indonesia Pintar/PIP) at SMA Negeri 1 Sungai Lilin, Musi Banyuasin Regency, using George C. Edwards III's policy implementation framework (communication, resources, implementer disposition, and bureaucratic structure). A descriptive qualitative case study design was employed. Data were collected through in-depth interviews, observation, and document analysis involving purposively selected participants including the principal, vice principal, school operator, student beneficiaries, and parents (total n = 22). Analysis followed the interactive model of Miles, Huberman, and Saldaña. Findings reveal that PIP implementation has improved educational access for economically disadvantaged students but faces four key constraints: (1) communication barriers due to parents' limited administrative literacy and digital access; (2) resource constraints including inadequate digital infrastructure and heavy operator workload; (3) generally positive implementer disposition, though bureaucratic rigidity persists; and (4) a bureaucratic structure with clear role division but insufficient integration of standard operating procedures and follow-up documentation. The study concludes that PIP's effectiveness depends on the integration of all four Edwards III dimensions. Strengthening data accuracy, digital infrastructure, service-oriented dispositions, and accountable bureaucratic governance is recommended. Limitations include single-site design and reliance on self-reported data. Future research should compare implementation across multiple schools and regions.